2013
DOI: 10.1186/1756-8935-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Identification and systematic annotation of tissue-specific differentially methylated regions using the Illumina 450k array

Abstract: BackgroundDNA methylation has been recognized as a key mechanism in cell differentiation. Various studies have compared tissues to characterize epigenetically regulated genomic regions, but due to differences in study design and focus there still is no consensus as to the annotation of genomic regions predominantly involved in tissue-specific methylation. We used a new algorithm to identify and annotate tissue-specific differentially methylated regions (tDMRs) from Illumina 450k chip data for four peripheral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
225
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(241 citation statements)
references
References 48 publications
14
225
1
1
Order By: Relevance
“…13 DMRs were assigned to genes using a distance-based strategy (C/¡ 10kb of gene boundaries) as described in the methods. Comparison of DMR-associated genes revealed that the highest number of shared genes (2004) were found between inguinal and epididymal adipocytes in the DIO mice, whereas only a few of the identified DMR-associated genes were shared between adipocytes from the 2 models ( Fig.…”
Section: Obesity Is Associated With Hypomethylationmentioning
confidence: 99%
“…13 DMRs were assigned to genes using a distance-based strategy (C/¡ 10kb of gene boundaries) as described in the methods. Comparison of DMR-associated genes revealed that the highest number of shared genes (2004) were found between inguinal and epididymal adipocytes in the DIO mice, whereas only a few of the identified DMR-associated genes were shared between adipocytes from the 2 models ( Fig.…”
Section: Obesity Is Associated With Hypomethylationmentioning
confidence: 99%
“…As described in detail by Slieker et al (2013), methylation sites were mapped to genomic features and DNase I hypersensitive sites (DHS). These genomic features consists of five gene-centric regions: (1) intergenic regions (>10 kb to -1.5 kb from the nearest transcription start site [TSS]), (2) proximal promotor (−1.5 kb to +500 kb form the nearest TSS), (3) distal promotor (−10 kb to −1.5 kb from the nearest TSS), (4) gene body (+500bp to 3 end of the gene) and (5) downstream region (3 end to +5 kb from 3 end).…”
Section: Genomic Annotationmentioning
confidence: 99%
“…Methylation sites were mapped to genomic features and DNase I hypersensitive sites (DHS) as described by Slieker et al (2013). Genomic features included five gene-centric regions: intergenic region (>10 kb from the nearest transcription start site [TSS]), distal promoter (-10 to -1.5 kb from the nearest TSS), proximal promoter (-1.5 kb to +500 bp from the nearest TSS), gene body (+500 bp to 3 end of the gene), and downstream region (3 end to +5 kb from 3 end).…”
Section: Annotationmentioning
confidence: 99%